2020
DOI: 10.1021/acs.jproteome.0c00254
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Profiling of Unannotated Microproteins and Alternative Proteins in Human Cell Lines

Abstract: Ribosome profiling and mass spectrometry have revealed thousands of small and alternative open reading frames (sm/alt-ORFs) that are translated into polypeptides variously termed as microproteins and alt-proteins in mammalian cells. Some micro-/alt-proteins exhibit stress-, cell-type-, and/or tissue-specific expression; understanding this regulated expression will be critical to elucidating their functions. While differential translation has been inferred by ribosome profiling, quantitative mass spectrometry-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 44 publications
0
51
0
Order By: Relevance
“…[28] Recently, Cao et al suggested a peptide-centric approach [31] to validate SEP identified with only one PSM. [17] We performed this additional filtering step and in total 39 out of 45 SEP identified in or study passed this criterion, while six peptides assigned to SEP identified with only one PSM were negative (Table 1). We further manually interpreted the six spectra of the peptides not passed the criterion and observed extensive precursor co-isolation of other peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Recently, Cao et al suggested a peptide-centric approach [31] to validate SEP identified with only one PSM. [17] We performed this additional filtering step and in total 39 out of 45 SEP identified in or study passed this criterion, while six peptides assigned to SEP identified with only one PSM were negative (Table 1). We further manually interpreted the six spectra of the peptides not passed the criterion and observed extensive precursor co-isolation of other peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we investigated classical SDS-PAGE based proteome separation followed by in-gel digestion with trypsin prior to LC-MS/MS (GeLC-MS) analysis for the identification of small proteins, and in particular SEP. [16,17] We assessed the influence of different SDS-PAGE gel staining methods prior to in-gel digestion: i) only fixing the gel, ii) zinc-imidazole negative staining, [18] and iii) Coomassie-staining, on the identification of SEP. As a model organism, we used the archaeon Methanosarcina mazei, grown under nitrogen starvation conditions; the same biological situation was used earlier to establish alternative strategies for SEP analysis. [11,14] The genome of this organism encodes for ≈3400 predicted proteins and additional about 1400 predicted SEP. [19][20][21]…”
Section: Introductionmentioning
confidence: 99%
“… a Control HEK 293T cells (lane 1) or alt-RPL36-GFP11-FLAG knock-in (KI) HEK 293T cells (lane 2) were transfected with alt-LEF1-FLAG (which is a recently identified ~20 kDa alt-ORF[ 1 ]), serving as a FLAG-IP control, and IPs were performed with anti-FLAG antibody followed by IB with anti-FLAG. Cell lysates (1%) before IP (input) were used as the loading controls.…”
Section: Resultsmentioning
confidence: 99%
“…Thousands of previously unannotated small and alternative open reading frames (smORFs, <100 amino acids, and alt-ORFs, >100 amino acids, respectively) have recently been revealed via genomic and proteomic technologies in mammalian genomes 1 , 2 . These genes previously escaped annotation not just because of their short length, but because, as a class, they exhibit low homology to proteins of known function, and are enriched for initiation at near-cognate non-AUG start codons (~50%) 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In a sense, the discovery of cncRNA blurred the boundary between ‘coding’ and ‘noncoding’ RNAs and led researchers to reconsider the function, evolution and understanding of RNAs ( 8 , 25 , 37 , 38 ). Recently, an increasing number of cncRNAs have been identified, including translated ncRNAs and untranslated mRNAs ( 18 , 39–41 ), and some studies began to identify cncRNAs by combining different high-throughput experimental technologies, such as mass spectrometry, ribosome profiling and CRISPR-based screening ( 18 , 24 , 42 , 43 ). Here, we developed cncRNAdb ( http://www.rna-society.org/cncrnadb/ ), a manually curated database of experimentally supported cncRNAs, which aims to provide a resource for efficient manipulation, browsing and analysis of cncRNAs.…”
Section: Introductionmentioning
confidence: 99%